Cadmium levels in the urine of cigarette smokers in Bangoan village, Tulungagung district - Lathifah, Qurrotu A’yunin; Hermawati, Andyanita Hanif; Kurniawati, Diva Febriani Rahma (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2023)
Cadmium (Cd) which accumulates in the body for a long time can damage human organs such as the respiratory tract, reproductive organs, liver, and kidneys. However, many smokers ignore this, so laboratory evidence is needed to advise smokers. This study analyzed the levels of cadmium (Cd) in the urine of smokers in Bangoan Village, Tulungagung District. The research method used is descriptive analytics. The research sample consisted of 15 smokers obtained through random sampling from 15 cafes in Bangoan Village, Tulungagung Regency. The research instrument was a urine examination result sheet. Urine samples were examined with an Atomic Absorption Spectrophotometer (AAS). The data analysis technique was carried out using quantitative descriptive. The results showed that 8 (53%) smokers had normal cadmium levels, and 7 (47%) other smokers had abnormal cadmium levels with the lowest level being 0.503 µg/L and the highest level being 83.892 µg/L. The community is expected to reduce cigarette consumption and avoid exposure to cigarette smoke in the surrounding environment in order to reduce organ damage.